THE ROLE OF EDUCATION IN THE NUTRITION TRANSITION AND ITS RELATION TO QUALITY OF LIFE (2015)
Education is a powerful tool to improve individuals quality of life; its role is evident by providing the necessary knowledge so that through autonomy, responsibility and a critical attitude, appropriate food choices are taken in order to provide welfare and health. In this paper, some factors affecting human nutrition will be discussed, the nutrition situation in Colombia, the importance of nutrition education and its relation to quality of life. It supports the idea that Colombia is currently experiencing a nutrition transition process and the problems it generates can be solved through education, affecting individuals quality of life.